Action of certain drugs in the determination of intrinsic pulmonary vascular mechanisms - Alcock, R. Patricia (The University of Edinburgh, 1936)
The actions of adrenaline, acetyl choline and histamine on the isolated perfused lungs of the dog were found to be in general the same as those published by Alcock, Berry and Daly.

The pressor response of adrenaline was not greatly enhanced by cocaine.

The pressor responses of adrenaline and acetyl choline could be reversed by ergotoxine.

The effect of ether on adrenaline was negligible.

The effect of ether on histamine was to convert an increase in outflow to a decrease.

The effect of adrenaline, acetyl choline and histamine on the isolated perfused lungs of the dog were tried under varying conditions.
Action of certain drugs in the determination of intrinsic pulmonary vascular mechanisms: written for the Gunning Victoria Jubilee Prize in Physiology